2016
DOI: 10.3389/fpsyg.2016.01904
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration of the Environmental Stress Hypothesis–Results from a Population-Based 6-Year Follow-Up

Abstract: The aim of this paper was to contribute to the elaboration of the Environmental Stress Hypothesis framework by testing eight hypotheses addressing the direct impact of gross motor coordination problems in elementary-school on selected physical, behavioral and psychosocial outcomes in adolescence. Results are based on a longitudinal sample of 940 participants who were (i) recruited as part of a population-based representative survey on health, physical fitness and physical activity in childhood and adolescence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 77 publications
1
26
0
2
Order By: Relevance
“…Most were from developed countries, with one study from Taiwan. Three prospective cohort studies were identified that screened for DCD in a cohort and assessed their internalising symptoms at a later follow up (Harrowell et al., ; male & female samples; Wagner, Jekauc, Worth, & Woll, ). The remaining 20 studies adopted a cross‐sectional design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most were from developed countries, with one study from Taiwan. Three prospective cohort studies were identified that screened for DCD in a cohort and assessed their internalising symptoms at a later follow up (Harrowell et al., ; male & female samples; Wagner, Jekauc, Worth, & Woll, ). The remaining 20 studies adopted a cross‐sectional design.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies identified individuals with and without DCD/probable DCD via population‐based screening of community samples (Campbell, Missiuna, & Vaillancourt, ; Chen, Tseng, Hu, & Cermak, ; Dewey et al., ; Francis & Piek, ; Harrowell et al., ; van den Heuvel, Jansen, Reijneveld, Flapper, & Smits‐Engelsman, ; King‐Dowling et al., ; Li et al., ; Missiuna et al., ; Piek, Bradbury, Elsley, & Tate, ; Schoemaker & Kalverboer, ; Skinner & Piek, ; Wagner et al., ). Of the remaining studies, five recruited DCD participants through selective or convenience samples such as clinical referrals or support groups (Crane, Sumner, & Hill, ; Hill & Brown, ; Pratt & Hill, ; Wagner, Bös, Jascenoka, Jekauc, & Petermann, ; Watson & Knott, ), one recruited participants through screening a clinical population of children born with extremely low birth weight (Davis et al., ), and one sampled from a monozygotic twin population (Piek et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Wagner, Jekauc, Worth, & Woll, 2016). Growing experimental and longitudinal evaluation of the Elaborated Environmental Stress Hypothesis is ongoing (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Growing experimental and longitudinal evaluation of the Elaborated Environmental Stress Hypothesis is ongoing (e.g. Wagner, Jekauc, Worth, & Woll, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the ALSPAC study provides a unique and valuable data set, with potentials for a differentiated elaboration of the environmental stress hypothesis and derived clinical implications as indicated in the study by Harrowell et al However, following the aforementioned controversial issues, researchers in the field working with the ALSPAC data set should: (1) reconsider alternative target group denotations and be aware of the presumably limited contextual impact of their problem definition; (2) integrate the stability of respective outcomes in terms of a cross‐lagged panel model; and (3) perform mediation analysis on the basis of at least three chronologically ordered measures.…”
mentioning
confidence: 99%